Investigation of Citrinin and Pigment Biosynthesis Mechanisms in Monascus purpureus by Transcriptomic Analysis - Liang, Bin; Du, Xin-Jun; Li, Ping; Sun, Chan-Chan; Wang, Shuo (Frontiers in Microbiology, 2018)
Monascus purpureus YY-1 is widely used in food colorant production in China. Our previous study clearly illustrated the whole-genome data for YY-1 and provided useful insight into evolutionary research and industrial applications. However, the presence of citrinin, which has nephrotoxic, hepatotoxic, and carcinogenic activities, has attracted attention to the safety of Monascus products. In an effort to reduce the harmful effects of citrinin in Monascus-related products, a random mutant of M. purpureus YY-1 with low citrinin production (designated as “winter”) was obtained in this study. To analyze the biosynthesis and regulation mechanisms of pigment and citrinin, a transcriptomic analysis of the M. purpureus YY-1 and winter strains was performed. Comparative transcriptomic analysis reveals pksCT, the essential gene for citrinin synthesis, showed a low expression level in M. purpureus YY-1 and winter, which suggested there might be isoenzymes in M. purpureus YY-1 that were responsible for the citrinin synthesis during evolution. In addition, changes in transcription factor expression may also influence the network regulating the citrinin synthesis pathway in M. purpureus. Moreover, the yields of pigments produced by the winter mutant were significantly increased. Repressing the central carbon metabolism and improving the acetyl-CoA pool can contribute to a high pigment yield, and enhanced NADPH regeneration can also lead to the metabolic flux of pigment production in M. purpureus. Investigations into the biosynthesis and regulation of citrinin and pigment production in M. purpureus will enhance our knowledge of the mechanisms behind the biosynthesis of fungal secondary metabolites.